أهم العناصر المؤثرة على صنع القرار الشرائي عند المستهلكين - ناصر محمد جودت; ديوب علي أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
-تبين هذه الدراسة أنه لكي يصبح عمل المؤسسات التجارية مع المشتري أكثر مردوداً وأشد فعالية، إنما ينبغي التنظيم الدقيق لكامل الأعمال الخاصة بتحقيق التجدد والنمو والازدهار، وضمان التأثير المتبادل والتعاون بين المنشآت الصناعية والتجارية من أجل العمل على تأمين التطابق والتناسب الموّجه بين الإنتاج والطلب، وجعل الطلب يحظى بقبول المشتري في سوق السلع الاستهلاكية. - وترصد أهم العناصر الضرورية في توجيه المستهلك نحو سلعة دون سواها من السلع المنافسة. - وتقدم تفسيراً نظرياً وعملياً للمنتجين والمسوقين والإداريين حول ضرورة الأخذ بما تمليه هذه العناصر من أجل تمكين منشآتنا من الاستجابة لمتطلبات الأسواق المحلية والخارجية، وتواكب ديناميكية أذواق المستهلكين. - وتستخدم هذه الدراسة المنهج الوصفي التحليلي في عرض انعكاسات هذه العناصر على سلوك المستهلكين. - وتختتم بتقديم مجموعة من المقترحات والتوصيات التي تشير إلى ضرورة تغيير أسلوب التفكير في التعامل مع قضية الإنتاج، وضرورة قيام الجهات المختصة بتوجيه شركاتنا نحو الاهتمام بالتسويق والترويج وتحديث الإمكانيات الفنية في هذه الصناعات، وما لذلك من تأثير على ضمان الشهرة والدخول إلى ميادين المنافسة. This study shows that in order to have a more profitable and effective relationship between commercial establishments and the buyer it is necessary to observe accurate organization of all the work needed for accomplishing renovation, growth and prosperity. Securing mutual cooperation between industrial and commercial plants is directed towards compatibility and proportionality between production and demand. It should finally make the demand meet the buyer’s consent in the market of consumer goods. This study concentrates on the most important factors needed to direct the consumer towards a particular commodity. It presents a theoretical and practical explanation for producers, marketers, and executives about such factors that might enable our plants to fulfill the requirements of the local and exterior market standards and consumers’ tastes. This study uses the descriptive and analytical method in offering the factors affecting consumers’ conduct. It concludes by giving a set of suggestions and recommendations related to production and marketing, which enable our national industry to be competitive worldwide.